Downshifting and antireflective thin films for solar module power enhancement. (March 2021) - He, Yujuan; Liu, Jie; Sung, Shi-Joon; Chang, Chih-hung
Abstract: Efforts to enhance the solar conversion efficiency have prevailed for decades. There is a growing interest in improving the spectral response of solar modules, especially in harvesting UV photons, which offer intense energy in a narrow wavelength range. To harvest UV photons and reduce reflection without interfering with the formulas and manufacturing process of solar cells, in this work, thin films that possess downshifting and antireflection capabilities were fabricated on the cover glass of multicrystalline Si solar cells. The thin films were composed of graded index layers of europium-doped yttrium orthovanadate (YVO4 :Eu) and hollow silica nanoparticles (HSNPs). The design of the composite thin films was assisted by the FDTD mathematical model that simulated the refractive index and thickness of each layer to obtain the optimum transmittance. The cover glass with multifunctional thin films harvested more than 30% of UV photons and enhanced the solar conversion efficiency by 4.12% at normal incidence compared to the uncoated cover glass. Graphical abstract: Unlabelled Image Highlights: Graded thin films are designed to enhance UV and visible photon utilization. The graded thin films increase the PCE of the pc-Si solar cell by 4.12%. The optical properties of graded thin films are simulated by the FDTD method.